Curriculum proposal for improving the organizational climate/Propuesta pedagógica para el mejoramiento del clima organizacional (Encuentros, 2019)
Working environment in companies had been exhaustively studied by careers like psychology and Business administration. Mostly, this studies develop methodologies for measuring the environment in a particular company or recommends the implementation of training strategies or workshops with the employees. However, this studies rarely talk about the pedagogical methodology and the didactics that the companies should use for get stronger a particular dimension of the environment. This article pretends to explore the effectivity of an aditional pedagogical methodology to improve the team work within a telecommunications company based in the way that the adult people learn and the strengthening of their socio-emotional skills.Keywords: organizational climate, adult teaching, cooperative work, interpersonal relations